Does Parental Divorce Affect Adolescents' Cognitive Development? : Evidence from Longitudinal Data - Anna Sanz-de-Galdeano; Daniela Vuri (Institute for the Study of Labor (IZA), 2004)
In this paper we analyse data from the National Education Longitudinal Study of 1988 to investigate whether experiencing parental divorce during adolescence reduces measured cognitive ability. To account for the potential endogeneity of parental divorce we employ a difference-in-differences model that relies on observing teenagers' outcomes before and after divorce. We find that parental divorce does not negatively affect teenagers' cognitive development. Our results also suggest that cross-section estimates overstate the detrimental effect of parental divorce.
Keywords: J12; 330; divorce; difference in differences; cognitive development; Ehe; Kinder; Kognition; Bildungsniveau; Schätzung; Vereinigte Staaten